Microstructural and Magnetic Properties of Polyamide-Based Recycled Composites with Iron Oxide Nanoparticles - Santos, Lucas G. Dos; Buelvas, Daina D. A.; Valezi, Daniel F. [UNESP]; Vicentin, Bruno L. S.; Rocha, Christian M. M.; Mauro, Eduardo Di; Porta, Felipe de A. La (MDPI, 2025)
This study explores a sustainable approach to developing magnetic nanocomposites by synthesizing a mixed-phase iron oxide (IO) and recycled polyamide (RPA) composite from textile waste. The RPA/IO nanocomposite’s microstructural and magnetic properties were characterized using X-ray diffraction (XRD) with Rietveld refinement, scanning, transmission electron microscopy (SEM, TEM), and vibrating sample magnetometry (VSM). The proportions of the Fe3O4 and γ-Fe2O3 phases were found to be 23.2 wt% and 76.8 wt%, respectively. SEM and TEM showed a porous, agglomerated IO surface morphology with an average particle size of 14 nm. Magnetic analysis revealed ferrimagnetic and superparamagnetic behavior, with VSM showing saturation magnetization values of 21.81 emu g−1 at 5 K and 18.84 emu g−1 at 300 K. Anisotropy constants were estimated at 4.28 × 105 and 1.53 × 105, respectively, for IO and the composite, with a blocking temperature of approximately 178 K at 300 K. These results contribute to understanding the magnetic behavior of IO and their nanocomposites, which is crucial for their potential applications in emerging technologies.
Keywords: environmental; maghemite; magnetite; nanocomposites; recycled polyamide composite